Evaluation of the implementation stimulation, detection, and early intervention for toddlers growth and development in Nanggalo Health Center - Azrimaidaliza, Azrimaidaliza; Resti, Resti; Helmizar, Helmizar (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: The coverage of Stimulation, Detection, and Early Intervention for Toddler Growth and Development (SDIDTK) toddlers at the Nanggalo Health Center has not yet reached the national target. This is influenced by the low participation of mothers of toddlers at Integrated Service Posts (Posyandus). The proportion of toddlers weighed at Posyandus 14.90%.Objective: The purpose of this study was to assess the implementation of the SDIDTK program at the Nanggalo Health Center to achieve the national target (90%).Materials and Methods: This type of qualitative research uses a systems approach. Data was collected through in-depth interviews, observation, and document review. Twelve informants were selected in the working area of the Nanggalo Health Center based on purpose sampling. Data processing involves the triangulation of sources and techniques. Records of in-depth interview results were made in the form of transcripts and analyses and interpreted in the form of research results.Results: Based on the research results obtained, there is a manual for implementing SDIDTK but no SOP has been found. The number of implementing staff is sufficient, but the distribution of the workload is not yet effective and efficient. The funds available for community health center activities are sufficient, but there has been no allocation of special funds to support SDIDTK activities. The facilities and infrastructure supporting the program are inadequate. The implementation of detection and stimulation is still not per the guidelines for all toddlers in the Nanggalo Community Health Center working area. Early intervention has been carried out for toddlers who are detected to be experiencing growth and development disorders. Records are summarized in cohorts and reported every month to the Health Service. Monitoring and evaluation are carried out in stages, but they are still not going well.Conclusion: The implementation of the SDIDTK program at the Nanggalo Health Center is still not good. Obstacles in program implementation come in the form of data problems, a lack of infrastructure, limited staff time, low community participation, and a lack of support from across sectors.